EVER DECREASING CIRCLES: THE EMPIRICAL, THEORETICAL AND (EVEN) IDEOLOGICAL PROBLEMS WITH CROSS‐STATE REGRESSION ANALYSIS IN INDIA. (21st March 2012) - McCartney, Matthew
<x xml:space="preserve">Abstract</x> This paper is concerned with the analysis of growth using cross‐country/ state growth regressions. The paper uses the example of state level growth in India and a case study of the growth experience of the state of Kerala in the 1990s. In practise empirical results using cross‐country/ state growth regressions remain disappointing. Orthodox analysis tends to stop with the assumption that it is only an empirical problem. This paper goes on to show that there are also theoretical and finally methodological–ideological problems why empirical results are poor. Each successive problem is engaged with by fewer and fewer researchers. In conclusion, this paper makes a case for the greater use of country case studies. Copyright © 2012 John Wiley & Sons, Ltd.